Severe Factor VII Deficiency Caused by a Novel Mutation His348 to Gln in the Catalytic Domain - Katsumi, Akira; Matsushita, Tadashi; Yamazaki, Tomio; Sugiura, Isamu; Kojima, Tetsuhito; Saito, Hidehiko (Thrombosis and Haemostasis, 2000)
Factor VII is a vitamin K-dependent zymogen that plays a key role in the initiation of the extrinsic pathway. A severe factor VII deficiency was identified in a 45-year old male whose plasma factor VII antigen was less than 60 ng/ml and expressed 5.2% of normal factor VII activity. DNA sequence analysis of the patient’s factor VII gene showed a thymidine to guanine transversion at nucleotide 10968 in exon VIII that results in a novel amino acid substitution of His348 to Gln. The patient was homozygous for this mutation, whereas some of his family members were heterozygous. Both wild type and mutant factor VII were transiently expressed in COS-1 cells. The level of secreted mutant factor VII antigen was only 11.0% of the level of wild type factor VII. In CHO cells stably transfected with the mutant factor VII, only 37.3% of the total labeled FVII was secreted into the conditioned media and the remainder was retained inside the cells. These data suggest this mutation leads to factor VII deficiency due to the impaired secretion of the molecule.
Keywords: Factor VII; catalytic domain; type I deficiency; impaired secretion